Future CO2-induced ocean acidification enhances resilience of a green tide alga to low-salinity stress. (15th July 2019) - Gao, Guang; Qu, Liming; Xu, Tianpeng; Burgess, J Grant; Li, Xinshu; Xu, Juntian
Abstract: To understand how Ulva species might respond to salinity stress during future ocean acidification we cultured a green tide alga Ulva linza at various salinities (control salinity, 30 PSU; medium salinity, 20 PSU; low salinity, 10 PSU) and CO2 concentrations (400 and 1000 ppmv) for over 30 days. The results showed that, under the low salinity conditions, the thalli could not complete its whole life cycle. The specific growth rate (SGR) of juvenile thalli decreased significantly with reduced salinity but increased with a rise in CO2 . Compared to the control, medium salinity also decreased the SGR of adult thalli at low CO2 but did not affect it at high CO2 . Similar patterns were also found in relative electron transport rate (rETR), non-photochemical quenching, saturating irradiance, and Chl b content. Although medium salinity reduced net photosynthetic rate and maximum rETR at each CO2 level, these negative effects were significantly alleviated at high CO2 levels. In addition, nitrate reductase activity was reduced by medium salinity but enhanced by high CO2 . These findings indicate that future ocean acidification would enhance U. linza' s tolerance to low salinity stress and may thus facilitate the occurrence of green tides dominated by U. linza .